2021
DOI: 10.1177/00912174211007675
|View full text |Cite
|
Sign up to set email alerts
|

Integration of mental health comorbidity in medical specialty programs in 20 countries

Abstract: Methods A systematic analysis was performed of the medical specialization academic programs of 20 different countries to establish which medical specialties take into account mental health issues in the specialty curricular design and which mental health content these programs address. The criteria that were explored in the educational programs include: 1) name of the medical specialties that take into account mental health content in curriculum design, 2) name of the mental health issues addressed by these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…A revision of educational requirements for healthcare professionals to improve their training curricula has also been proposed in order to adequately prepare the young generation of professionals to manage physical comorbidities in patients with severe mental disorders. In particular, the WPA, the world’s largest professional association of psychiatrists and mental health professionals [ 72 , 73 ], has recently established a WPA Working Group on Physical Comorbidities [ 74 , 75 ], so to promote attention to management of physical comorbidities in people with severe mental disorders, to update training materials available on the educational portal of the Association [ 76 ], to organize webinars and seminars with international experts in the field [ 77 79 ] and to promote the dissemination of good clinical practice for improving physical health in patients with severe mental disorders [ 80 83 ].…”
Section: Main Textmentioning
confidence: 99%
“…A revision of educational requirements for healthcare professionals to improve their training curricula has also been proposed in order to adequately prepare the young generation of professionals to manage physical comorbidities in patients with severe mental disorders. In particular, the WPA, the world’s largest professional association of psychiatrists and mental health professionals [ 72 , 73 ], has recently established a WPA Working Group on Physical Comorbidities [ 74 , 75 ], so to promote attention to management of physical comorbidities in people with severe mental disorders, to update training materials available on the educational portal of the Association [ 76 ], to organize webinars and seminars with international experts in the field [ 77 79 ] and to promote the dissemination of good clinical practice for improving physical health in patients with severe mental disorders [ 80 83 ].…”
Section: Main Textmentioning
confidence: 99%
“…In terms of medical graduate training, a recent systematic review of medical specialty programs (internal medicine, family medicine, neurology, pediatrics and geriatrics) across 20 countries found that less than 50% of the academic programs included content on mental health. 39 Further, of the 20 countries, Germany, France, and Croatia excluded context on anxiety disorders in their postgraduate specialty programs. In general, the variability in length of mental health education at the undergraduate level and lack of emphasis on practical teaching combined with a lack of mental health education at the graduate level (and for some countries, direct exclusion of anxiety disorders) sets the stage for the misdiagnosis of OCD.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio is perhaps a primary index of the state of the art in child and adolescent mental health education in primary care, especially given the essential centrality of youth mental disorder and lifespan health. [15][16][17]…”
Section: Discussionmentioning
confidence: 99%
“…Only about 24% of the participating physicians were evaluable as they had made referrals to child and adolescent mental health services over the last 18 years. This ratio is perhaps a primary index of the state of the art in child and adolescent mental health education in primary care, especially given the essential centrality of youth mental disorder and lifespan health [ 15 - 17 ].…”
Section: Discussionmentioning
confidence: 99%